Domesticating Bergman's The Seventh Seal in Akhavan Sales' "Then, after the Thunder" - Zahra Khoshamen; Akbar Shayanseresht (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
As sources of inspiration, foreign literary and artistic works can effect change in contemporary Persian literature. In some cases, this inspiration has been provided by cinematic works. In the process, Iranian writers have often domesticated the source text to adapt it to the Iranian culture.  For instance, Akhavan Sales' "Then, after the Thunder" inspired by Bergman's philosophical film, The Seventh Seal has changed the original in many respects to appease the local readers. The present study intends to explicate the domestication strategies used in the move from the source text to the destination text, based on Yuri Lotman's theory of semiotics. The paper shows that Akhavan Sales mostly tries to stay within the boundaries of tradition by limiting his functional space. For this purpose, he draws on linguistic localization in the form of linguistic archaism, application of common slang words and expressions, and the social function of language. Moreover, Akhavan Sales applies pictorial, historical, geographical, political and social domestication to bring the foreign text closer to the destination culture. Nevertheless, in a few cases, the poet innovates by taking liberties in his explicitly employing non-indigenous elements.